2013
DOI: 10.1021/jp3093989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sn and Cr Doping on Morphology and Luminescence of Thermally Grown Ga2O3 Nanowires

Abstract: Elongated micro-and nanostructures of Sn doped or Sn and Cr codoped monoclinic gallium oxide have been grown by a thermal method. The presence of Sn during growth has been shown to strongly influence the morphology of the resulting structures, including Sn doped branched wires, whips, and needles. Subsequent codoping with Cr is achieved through thermal diffusion for photonic purposes. The formation mechanism of the branched structures has been studied by transmission electron microscopy (TEM). Epitaxial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…On the other hand, the UV-blue band is redshifted from about 366 nm to some 400 nm and broadened when temperature increases. A similar behaviour of this band was observed for Sn, Cr, codoped gallium oxide nanostructures [9]. The sharp infrared peak keeps a similar width and shows only a slight redshift of about 2 nm.…”
Section: (E)supporting
confidence: 81%
See 4 more Smart Citations
“…On the other hand, the UV-blue band is redshifted from about 366 nm to some 400 nm and broadened when temperature increases. A similar behaviour of this band was observed for Sn, Cr, codoped gallium oxide nanostructures [9]. The sharp infrared peak keeps a similar width and shows only a slight redshift of about 2 nm.…”
Section: (E)supporting
confidence: 81%
“…transversal pyramids that grow on the lateral sides of the main rods. It has been previously reported that during vapour-solid (VS) growth the presence of different doping elements in the precursors can result in notable morphological changes, such as the formation of branches [9], crossing wires [17] and complex hierarchical structures [18]. However, these morphological pyramidal features have not been observed with other dopants or in undoped gallium oxide microstructures grown under similar conditions, as shown in figure 1(e).…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations